Lithofacies Analysis and Reconstruction of Deformation Types of Cenozoic Sediments of Phú Khánh Basin - Nghi, Trần; Thân, Trần Hữu; Ngợi, Chu Văn; Tuấn, Nguyễn Duy; Dung, Trần Thị; Thảo, Nguyễn Thị Phương; Hằng, Phạm Thị Thu; Sơn, Trần Văn (VNU Journal of Science: Earth and Environmental Sciences; Vol 29 No 1, 2013)
Abstract : From Oligocene and Quaternary geological sedimentary section have six cycles corresponding to six sequences: - Sequence 1: Eocene - early Oligocene (E 2 – E 3 1 ); - Sequence 2: Late Oligocene (E 3 2 ); - Sequence 3: Early Miocene (N 1 1 ); - Sequence 4: Middle Miocene (N 1 2 ); - Sequence 5: Late Miocene (N 1 3 ); - Sequence 6: Pliocene - Quaternary (N 2 - Q). Since then may establish three general integrated formulas between the lithofacies association series and sedimentary systems tract as follows: Sedimentary lowstand systems tract (LST): LST = arLST + (ar + amr)LST + (amt + mt)/(amr + mr) LST + mrLST (1); Sedimentary transgressive systems tract (TST): TST = MtTST + atTST + (amr + mr)/(mt + amt)TST + mtTST (2); Sedimentary highstand systems tract (HST): HST = arHST + (ar + amr)HST + (amt+mt)/ (amr +mr)HST + mrHST (3). Keywords: Sequence, lowstand, highstand, transgressive systems tract, parasequence set, parasequence, marine flooding plain.